A Holding Space - Hunter, Vicky (Ecocene: Cappadocia Journal of Environmental Humanities, 2022)
This writing introduces early reflections on a site dance micro project titled ‘A ‘Holding Space’ conducted from June to Sept 2021 in West Sussex, UK. The work was performed by dancers Natasha Margerison and Kate Welch, choreographed by Vicky Hunter and filmed and edited by Jack Leslie. During lockdown the lack of touching and holding our loved ones was expressed as a significant loss by many. As we emerged from lockdown in the summer of 2021, individuals, friends, and families were able to touch and hug each other. However, this also required a process of adjustment to the ‘new normal’ in which proximity and touch with those outside support bubbles and family groups needed to be navigated and managed. Alongside this phenomenon, during lockdown a significant number of people discovered renewed pleasure and comfort through engagement with nature spaces and woodland sites. The writing discusses some of the motivations and theoretical ideas informing the work and presents key questions and creative approaches explored during the creative process that led to the presentation of a live dance work, participant workshops and the production of a site dance film (link provided) that captures some of the project’s key outcomes.